The Influence of Service Quality and Image on Outpatient Loyalty at Yos Sudarso Hospital, Padang - Harry Afprimma Dona; Erni Masdupi; Vidyarini Dwita (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to analyze (1) the effect of service quality on patient loyalty at Yos Sudarso Padang Hospital , (2) the effect of service quality through image on patient loyalty at Yos Sudarso Padang Hospital, (3) the effect of image on patient loyalty at Yos Hospital sudarso padang. This research was a caseative study. The population in this study were patients who had been treated at Yos Sudarso Hospital, Padang. Sampling used the Accidental Sampling method. instrument testing was carried out by testing the validity and reliability tests, data analysis using path analysis. The results showed that (1) service quality had a significant effect on the image of Yos Sudarso Padang Hospital, (2) service quality had a significant effect on patient loyalty at Yos Sudarso Padang Hospital, (3) image had a significant effect on patient loyalty on Yos Sudarso Padang Hospital.